PENGARUH BAHAN PENGENCER SARI KACANG KEDELAI (Glycine max) TERHADAP VIABILITAS DAN NEKROSIS SPERMATOZOA DOMBA SAPUDI - Immelda, Kicky Hanis; Susilowati, Suherni; Yudaniayanti, Ira Sari (Universitas Airlangga, 2019)
The purpose of study was to find out the effect of different concentrations of soya bean extractin sperm diluter, stored at 5°C toward sperm viability and necrosis. The semen was divided into four groups : P0: 0.1 ml sapudi ram + 1 ml of diluent yolk citrate, P1: sapudi ram 0.1 ml + 1 ml diluent soybeans extract konsentration 5%, P2: 0.1 ml sapudi ram + 1 ml diluent soybeans extract konsentration 10%, P3: 0.1 ml sheep semen + 1 ml diluent soybeans konsentration 15%. The result showed that the dose of soya bean extract diluter konsentration of 15% could increase the viability percentage and could decrease the necrosis percentage of sperm.